Pulmonary regurgitant volume is superior to fraction using background-corrected phase contrast MRI in determining the severity of regurgitation in repaired tetralogy of Fallot - Gorter, Thomas M. (Int J Cardiovasc Imaging, 2015)
In the assessment of pulmonary regurgitation (PR) using phase contrast MRI, phase offset errors affect the accuracy of flow. This study evaluated the use of automated background correction for phase offset in the quantification of PR fraction and volume in patients with repaired tetralogy of Fallot (TOF), and to assess its clinical impact. We retrospectively analyzed 203 cardiac MRI studies, performed on 1.5-T scanner. Pulmonary flow (Q(P)) and systemic flow (Q(S)) was assessed both with and without background correction. Non-corrected and corrected Q(P) was correlated with Q(S). PR was correlated with (1) indexed right ventricular end-diastolic volume (RVEDVi) and (2) with differential right and left ventricular stroke volumes (PR(SV)). Both PR fraction and volume showed major change after correction (−43 to +36 % and −13 to +13 ml/m(2)). Corrected Q(P) and Q(S) were stronger correlated with each other than non-corrected Q(P) and Q(S) [r = 0.78 vs. 0.73 (p < 0.001)]. Both PR fraction and volume were stronger correlated with RVEDVi, compared to their non-corrected counterparts (p < 0.001). PR volume was stronger correlated with RVEDVi, compared to PR fraction [r = 0.74 vs. 0.69 (p < 0.001)]. When patients were divided according to PR severity, 12 % of patients reclassified after correction. Background correction for phase offset significantly changed the quantification of PR. Non-corrected assessment of PR may result in the misclassification of patients. Our data suggest that the use of PR volume is favourable in the follow-up of patients with repaired TOF. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10554-015-0670-6) contains supplementary material, which is available to authorized users.